THE EFFECTIVENESS OF ZAKAT, INFAQ, AND SADAQAH (ZIS) COLLECTION AT BAZNAS HULU SUNGAI TENGAH REGENCY AMONG REGIONAL WORK UNITS (SKPD) - Anna Maryati; Agus Surya Dharma; Nur Mahbubah (PPPM STIA Amuntai, 2026)
This study evaluates the performance of the Hulu Sungai Tengah Regency BAZNAS (National Zakat Agency) in collecting ZIS funds within the Regional Work Units (SKPD), which is driven by the phenomenon of minimal zakat realization from civil servants (ASN) and weak regulatory synergy with the local government. Using descriptive qualitative methods through purposive sampling of leaders, staff, and ASN, this study reveals that although the digitalization strategy and the